Macromolecular Anticancer Therapeutics - Reddy, L. Harivardhan; Couvreur, Patrick; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The field of macromolecular therapeutics for cancer therapy is of considerable importance, as these therapeutic systems are gaining more and more interest to give new directions for the treatment of this dreadful disease. Macromolecular Anticancer Therapeutics, which describes in detail the macromolecular therapeutics for cancer therapy, covers the classification of these anticancer drugs based on therapeutic targets, and elaborates on different classes of anticancer therapeutics which are either in pre-clinic or in clinical phases or are already commercialized. This book also discusses various signal transduction pathways involved in the cancer growth and resistance to therapy, providing a clear insight into the molecular mechanistic aspects of this topic; it also describes the essential targets for efficient cancer therapy. In detail, this volume elaborates the different categories of macromolecular therapeutics of respectively natural and synthetic polymer and lipid origin, their chemistry, design and development, opportunities and challenges, current status, pre-clinic and clinical progresses. In addition, the design, development, and the challenges involved in future directions for cancer therapy using various categories of antibody-based therapeutics are elaborated in areas such as antibody-mediated drug targeting to cancer employing antibody-drug conjugates, radioimmunoconjugates, toxin-antibody conjugates, antibody-mediated enzyme pro-drug therapeutics, and also using antibodies alone to interfere with specific molecular targets responsible for tumor growth and progression. Besides the current status, pre-clinic and clinical progress of a variety of therapeutic anticancer oligonucleotides and siRNA designed and developed for specific inhibition of oncogenes are detailed. Furthermore, in this book, special attention is given to the treatment of breast cancer based on a comprehensive description about molecular mechanisms involved, hormone receptors implicated and molecular therapeutic interventions. Macromolecular Anticancer Therapeutics details the current macromolecular therapeutic strategies, and should become an important reference for practitioners, oncologists, medical pharmacologists, medicinal chemists, biomedical scientists, experimental pharmacologists and pharmaceutical technologists. It is also a reference concerning macromolecular cancer therapy for graduates, post-graduates and Ph.D. students belonging to these fields.
Keywords: Medicine; Oncology; Toxicology; Biomedicine; Cancer Research; Pharmacology/Toxicology.